Bio-grafted silica to make an asphalt road a sink for reactive environmental pollutants. (15th November 2022) - Shariati, Saba; Rajib, Amirul I.; Crocker, Michael S.; Ackerman-Biegasiewicz, Laura K.G.; Martis, Vladimir; Fini, Elham H.
Abstract: Asphalt-surfaced areas such as roads have been reported as major non-combustion sources of reactive organic compounds in urban areas. Emission of latter compounds from asphalt is exacerbated due to exposure to sunlight and high temperature, contributing to negative human and environmental health outcomes. Furthermore, loss of asphalt components over time is linked to bitumen's aging that reduces service life of roads. Here, we introduce a designed bio-grafted-silica nano-filler derived from wood pellet as a sink for latter volatile compounds in an asphalt mixture. Molecular modeling calculations showed the remarkable adsorptive activity of the bio-grafted silica for trapping select asphalt volatiles, especially for the sulfur-containing aromatics and the oxygen-containing aromatics. Laboratory experiment revealed that the bitumen modified with bio-grafted silica exhibited up to 23% lower signs of aging. Thermogravimetric analysis proved that the modified bitumen exhibited a 16% reduction in mass loss compared to neat bitumen. Dynamic vapor sorption analysis also showed bio-grafted silica adsorbed higher amounts of a candidate volatile than pristine silica. The study outcomes highlights the advantages of a bio-derived modifier in asphalt to address concerns associated with the loss of hazardous compounds. Graphical abstract: Image 1 Highlights: Bio-grafted silica nano-filler traps volatile organic compounds in asphalt mixture. Bio-grafted silica nano-filler has high adsorption affinity toward organic volatiles. Bio-grafted silica modifier delays aging and mass loss in bitumen. Bio-grafted silica is made by selective adsorption of bio-oil molecules onto silica.